29.1: Invited Paper: A Study on the Micro‐Lens Arrays Combination based Optical Film for Optical Field Optimized Projection Display. (4th October 2019) - Ding, Liang; Li, Zhou; Su, Dongbian; Guo, Bingang; Wang, Pengfei; Guo, Dengji; Liu, Cai
Abstract : Owning to the fast development of projection technologies, the large‐scale projection has great potential application for various viewing circumstances in open spaces. This paper reports a novel type of optical imaging film (G2‐HK‐FP) which comprised of a combination of micro‐lens arrays of different sizes and an ambient light rejection design. This film exhibited comparable displaying performance with silver screen film in the dark environment, and superior performance in the ambient light condition in the aspects of relative contrast, color gamut and ambient light rejection efficiency.